Lithic Procurement and Provisioning at the Lower Palaeolithic Site of Shishan Marsh 1 in the Azraq Basin, Jordan - Beller, Jeremy A.; Murray, John K.; Alsouliman, Amer S. (Jordan Journal for History and Archaeology, 2024)
Considerations of the landscape, the distribution and quality of resources, distances to outcrops, and proximity to other resources factor into the procurement decision-making by prehistoric foragers. However, the patterns of resource exploitation and utilisation are likely to vary by region, and those exhibited in marginal environments are not fully explored. This report focuses on the nature of lithic procurement and provisioning at the Lower Palaeolithic site of Shishan Marsh 1 in the Azraq Basin, Jordan. It draws upon several lines of evidence, including provenance and use-wear analyses performed on the biface assemblage. The results indicate raw material exploitation occurred at local and non-local distances to the site and the lithics were used for a variety of activities on medium-hard materials. Foragers moved toward the wetlands from significant distances on the surrounding landscape, likely bringing finished tools and, after use, discarding them in relatively good condition. The accumulation over time of ready-to-use tools at Shishan Marsh 1 points to a provisioning of the wetland margins for future needs.